Cu2ZnSnS4:graphene oxide nanocomposites based photoresponse devices - Al-Hazmi, Faten; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2015)
Graphene oxide: Cu2ZnSnS4 nanocomposites were synthesized by the chemical method to fabricate photodiodes. The structural properties of the nanocomposites were analyzed using a Scanning electron microscopy (SEM) and X-ray Energy Dispersive energy (EDS) technique. Electrical and photoresponse properties of the p-Si/graphene oxide: Cu2ZnSnS4 nanocomposites diodes were investigated by current-voltage and capacitance-conductance-voltages characteristics under dark and various illumination conditions. The photocurrent of the diodes is larger than the dark current suggesting that the prepared diodes exhibited photodiode behavior. The photoconducting mechanism of the diodes was analyzed and it was found that the photoconduction mechanism is controlled by the monomolecular recombination. The diodes exhibited also a photocapacitor behavior. The photoelectrical properties of Au/GO:Cu2ZnSnS4/p-Si/Al devices indicate that the prepared diodes can be used both as a photodiode and a photocapacitor in optoelectronic device applications. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Sensors; Photodiode; Nanocomposites